INOVASI TEKNOLOGI SMART MOBILITY BUS LISTRIK DI KOTA BANDUNG UNTUK MENINGKATKAN KUALITAS LAYANAN TRANSPORTASI PUBLIK - Carissa Adhara; Rianti Najwa Khairunnisa; Najwa Mayang Dayatri; Salviaputri Irsha Khamini; Ivan Darmawan (Triwikrama: Jurnal Ilmu Sosial, 2024)
This research aims to deploy smart mobility technology on electric buses in Bandung City and analyze its impact on the quality of public transportation services. Through quantitative and qualitative approaches, this research examines technical, operational and user perception aspects. The research results show that the application of intelligent mobility technology such as passenger information systems, electronic payments, and integration with other modes of transportation has increased operational efficiency, user comfort, and the level of public satisfaction. However, there are still several challenges that need to be overcome, such as limited charging infrastructure and expanding network routes. This study provides policy recommendations to accelerate the development of sustainable electricity-based public transportation in the city of Bandung.